Role of Desmoglein Autoantibody in the Diagnosis of Pemphigus Vulgaris: A Case Report - Diane Lukito Setiawan; Munawaroh Fitriah; Awalia Awalia (Acta Medica Indonesiana, 2025)
Pemphigus vulgaris (PV) is a group of autoimmune diseases that cause abnormalities in the form of lesions or blisters on the skin and mucous membranes. It often presents diagnostic challenges due to its varied clinical manifestations. Accurate diagnosis and treatment are essential to reduce mortality in patients with PV. Traditional diagnostic methods, such as histopathology and direct immunofluorescence, may not always provide conclusive results, especially if the patient does not have an intact bulla. Our report emphasizes the role of desmoglein autoantibody testing using enzyme-linked immunosorbent assay to confirm the diagnosis, allowing for prompt and targeted therapeutic interventions.